2016
DOI: 10.5535/arm.2016.40.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laryngopharyngeal Neuromuscular Electrical Stimulation on Dysphonia Accompanied by Dysphagia in Post-stroke and Traumatic Brain Injury Patients: A Pilot Study

Abstract: ObjectiveTo investigate the effect of laryngopharyngeal neuromuscular electrical stimulation (NMES) on dysphonia in patients with dysphagia caused by stroke or traumatic brain injury (TBI).MethodsEighteen patients participated in this study. The subjects were divided into NMES (n=12) and conventional swallowing training only (CST, n=6) groups. The NMES group received NMES combined with CST for 2 weeks, followed by CST without NMES for the next 2 weeks. The CST group received only CST for 4 weeks. All of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…[ 14 16 ] Dysarthria (including wet voice) and dysphagia have similar pathogeneses in stroke patients, especially those related to the laryngopharyngeal functions. [ 17 ] The acoustic change in phonation following a swallow is a high-risk indicator of fluid aspiration. [ 18 ] Moreover, the subglottal pressure initiates and maintains the vocal fold vibration that facilitates voice production.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 16 ] Dysarthria (including wet voice) and dysphagia have similar pathogeneses in stroke patients, especially those related to the laryngopharyngeal functions. [ 17 ] The acoustic change in phonation following a swallow is a high-risk indicator of fluid aspiration. [ 18 ] Moreover, the subglottal pressure initiates and maintains the vocal fold vibration that facilitates voice production.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the same search as mentioned above (see 4a), 35 RCTs 173, 281-314 and 6 NRCT [315][316][317][318][319][320] were included in the meta-analysis (Table 15, supplement 11). All trials reported data on swallowing performance using a variety of different scales and nearly all trials used a local…”
Section: In Patients With Post-stroke Dysphagia Do Neurostimulation Techniques Compared To Behavioural Treatments Improve Functional Outcmentioning
confidence: 99%
“…In addition, in some studies, a three-arm design was adopted, where either two different interventions were compared against a sham condition or a combination of treatments were studied against each single intervention. To account for these differences in trial design, the WG formulated two PICO questions: Based on the same search as mentioned above (see 4a), 35 RCTs 173, 281-314 and 6 NRCT [315][316][317][318][319][320] were included in the meta-analysis (Table 15, supplement 11). All trials reported data on swallowing performance using a variety of different scales and nearly all trials used a local The number of trials included into the different meta-analyses pertinent to this topic is, in part, quite high and most results of single trials have a similar trend which in most cases is also in line with results from non-randomized trials.…”
Section: Strength Of Recommendation: Weak For Intervention ↑?mentioning
confidence: 99%
See 1 more Smart Citation
“…NMES is a non-behavioral therapy for dysphagia and the frequency range for the systems is 10 to 50 Hz, which induces muscle contraction or simulates normal autonomic movement through excitatory contraction to improve or restore the function of stimulated muscles or muscle groups [ 16 ]. A number of studies have confirmed that NMES treatment improves the degree of laryngeal elevation and of openness and coordination of the pharyngeal muscles, reduces aspiration, and improves swallowing function [ 32 36 ]. In addition to the kinesthetic response, the frequency can induce sensory stimulation below the electrodes, triggering reflexes in the pharynx, trigeminal, and vagal nerves, among others, which send sensory feedback to the central pattern generator (CPG) and the cortex and subcortical center.…”
Section: Discussionmentioning
confidence: 99%